2021
DOI: 10.1002/acr.24797
|View full text |Cite
|
Sign up to set email alerts
|

Association of Disease Activity and Disability With Rehabilitation Utilization in African American Adults With Rheumatoid Arthritis

Abstract: Objective. To examine the association of disease activity and disability with rehabilitation utilization in African American adults with rheumatoid arthritis (RA).Methods. We analyzed cross-sectional baseline data from the Consortium for the Longitudinal Evaluation of African Americans with RA (CLEAR) I and CLEAR II registry. Disease activity was quantified with the Disease Activity Score in 28 joints using the C-reactive protein level. Disability was measured with the Health Assessment Questionnaire. Rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A high dose of rehabilitation was associated with more favorable changes in physical function, pain, and fatigue compared to a low dose of rehabilitation; however, only the association with physical function changes were maintained in the adjusted models. Rehabilitation utilization for RA in the US is low (14-15% in 6 months [22,23]) and varies greatly. Iversen et al reported that 28% of those who used PT reported attending 1-4 visits, while 53% reported attending >8 visits (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high dose of rehabilitation was associated with more favorable changes in physical function, pain, and fatigue compared to a low dose of rehabilitation; however, only the association with physical function changes were maintained in the adjusted models. Rehabilitation utilization for RA in the US is low (14-15% in 6 months [22,23]) and varies greatly. Iversen et al reported that 28% of those who used PT reported attending 1-4 visits, while 53% reported attending >8 visits (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known regarding rehabilitation utilization patterns in adults with RA in the US. Two cross-sectional studies reported that 14-15% of adults with RA used PT over a 6-month period (22,23). These rates of PT utilization likely overestimate utilization for RA, specifically because people often use PT for reasons unrelated to RA (22).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, our collective experiences speaking with persons with RA, including patient advisory board members for organizations, patient panel participants, and individuals, consistently reflect a general lack of awareness of physical therapy and an absence of physical therapy in the therapeutic options presented by their rheumatology provider to address common and persistent functional limitations. These anecdotal experiences are supported by the finding that 50% of a US cohort of older adults with longstanding RA (median 10 years since diagnosis) reported they had never used physical therapy or occupational therapy (9).…”
Section: What Are the Recommendations For Physical Therapy?mentioning
confidence: 92%
“…Evidence-based guidance on the use of physical therapy and exercise in the integrative care of patients with RA is only useful if patients are aware of these options. Multiple studies using various methodologies demonstrate consistently low utilization of physical therapy among adults with RA, with estimates ranging from 10% to 15% in the prior 6 to 12 months (9)(10)(11). Indeed, utilization of formal physical therapy services are not necessary for all patients at all times.…”
Section: Challenges and Recommendations For Guideline Implementationmentioning
confidence: 99%
“…The medicines used for this purpose are primarily immunosuppressive or immune-modulating drugs. 7 These immunosuppressive medications include Methotrexate, Leflunomide, Sulfasalazine, Hydroxy-chloroquine, Azathioprine, and Mycophenolate mofetil. 8,9 Since these medicines suppress or modify the immune system, they are not without side effects.…”
Section: Introductionmentioning
confidence: 99%